The Role of p27kip1 in the Aggressiveness of Papillary Thyroid Carcinoma: A Clinicopathological Analysis - Ibrahim, Wafaa K.; Al-khafaji, khitam R. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Cell-cycle-regulating proteins, including cyclin-dependent kinase inhibitor 1B p27kip1, have been researched in different malignancies, including thyroid carcinoma, and their association with tumor aggressiveness and recurrence has been examined in many tumors. Objective: This research aimed to examine the clinicopathological relevance of reduced cyclin-dependent kinase inhibitor 1B p27kip1 expression in papillary thyroid carcinoma and its association with the clinicopathological parameters indicative of papillary thyroid carcinoma aggressiveness. Methods: Formalin-fixed, paraffin-embedded tissue blocks were obtained from histologically confirmed cases of papillary thyroid carcinoma diagnosed between June 2022 and June 2023 at the National Center for Teaching Laboratories, Medical City Complex, Baghdad, Iraq. A total of 60 papillary thyroid carcinoma samples were included in the study. Immunohistochemical analysis was performed to assess the expression of the p27 protein. The study further evaluated the association between cyclin-dependent kinase inhibitor 1B p27kip1 expression and various clinicopathological parameters, including patients’ age, sex, papillary thyroid carcinoma subtypes, tumor size, capsular invasion, multifocality, extrathyroidal extension, and lymph node metastasis. Results: A decrease in the expression of cyclin-dependent kinase inhibitor 1B p27kip1 of less than 10% was observed in 37 out of 60 cases (61.7%). The correlation with clinicopathological parameters revealed a significant decrease in expression of cyclin-dependent kinase inhibitor 1B p27kip1 associated with female sex, classical variant PTC, infiltrative tumors, large tumor size (2-2.5 cm), and multifocal lesions. Conclusion: Reduced expression of cyclin-dependent kinase inhibitor 1B p27kip1; (<10%) was observed at a relatively high rate in papillary thyroid carcinoma. A significant correlation was found between decreased cyclin-dependent kinase inhibitor 1B p27kip1 expression and several clinicopathological features, including infiltrative pattern tumors, large tumor size, and multifocality. These findings suggest that reduced cyclin-dependent kinase inhibitor 1B p27kip1 expression may be linked to more aggressive tumor behaviour and could potentially serve as a prognostic marker in PTC.